COVID-19 pandemic impact on follow-up of child growth and development in Brazil - Lucas Lima Carneiro; Ed Wilson Rodrigues Vieira; Elysângela Dittz Duarte; Najara Barbosa da Rocha; Gustavo Velasquez-Melendez; Walmir Caminhas (Frontiers Media S.A., 2022)
ObjectivesThis study investigated the impact of the COVID-19 pandemic on the primary health care (PHC) services to follow-up the child growth and development (CGD) in Brazil.MethodsA cross-sectional study was conducted using secondary data related visits to assess the growth and development of children up to five years between Apr-2017 to Mar-2021. Differences between monthly rate of visits (per thousand inhabitants up to five) during the pandemic (Apr-2020 to Mar-2021) and before (Apr-2017 to Mar-2020) were analyzed using paired t test and control diagrams (averages ± 1.96 standard deviation).ResultsA total of 39,599,313 visits for monitoring CGD was studied. The average monthly rate of visits dropped from 61.34 (per thousand) before the pandemic to 39.70 in the first 12 months of the pandemic (p < 0.001). In all states, except Rio Grande do Sul, there was a significant reduction, with differences ranging from −14.21% in São Paulo to −59.66% in Ceará. The Northeast region was the most impacted, being lower than expected in all 12 first months of pandemic.ConclusionsThe number of visits to follow-up the CGD in PHC in Brazil decreased during the first year of the COVID-19 pandemic, varying over the months and between states and regions.